Evaluating Categories From Experience: The Simple Averaging Heuristic. - Woiczyk, Thomas K. A.; Le Mens, Gaël (Journal of Personality & Social Psychology, 2021)
We analyze how people form evaluative judgments about categories based on their experiences with category members. Prior research suggests that such evaluative judgments depend on some experience average but is unclear about the specific kind of average. We hypothesized that evaluations of categories could be driven either by the simple average of experiences with the category or by the member average (the average of the evaluations of the category members, where the evaluation of a category member is the average of experiences with this particular member). Understanding whether evaluations of categories are driven by the simple average or the member average is important in settings where people obtain unbalanced numbers of observations about category members such as when people form opinions about a social group and predominantly interact with just a few members of this group. Across nine studies (N = 1,966), we consistently found that evaluative judgments about categories were better explained by the simple average than by the member average. We call the underlying cognitive strategy the simple averaging heuristic. Collected evidence indicates that participants relied on simple averaging even in settings where normative principles required avoiding the use of this cognitive strategy, leading to systematic mistakes. Our findings contribute to several areas of social cognition such as research on redundancy biases, information aggregation, social sampling, and norm perceptions.